Organocatalytic ring-opening polymerization of disulfide functional macrocyclic carbonates: An alternative strategy to enzymatic catalysis. (15th January 2020) - Yan, Bingkun; Liang, Bingyu; Hou, Jiaqian; Wei, Chao; Xiao, Yan; Lang, Meidong; Huang, Farong
Graphical abstract: The ROP of disulfide functional macrocyclic carbonate by organocatalysts was reported for the first time with higher effectiveness, milder condition and more controlled manner than enzyme catalyst N-435, which provided a robust and new approach toward more facile ROP of macrocyclic carbonates. Highlights: The successful ROP of disulfide functional macrocyclic carbonates (MSS) expanded the ROP of macrocycles. Organic catalyst TBD could effectively activate the ROP of MSS, affording tailor-made disulfide functional aliphatic polycarbonates with high end group fidelity, high molecular weight and narrow molecular-weight distribution. TBD exhibited higher effectiveness, milder condition and more controlled manner than enzyme (N-435) in the ROP of macrocyclic carbonates. Abstract: Ring-opening polymerization (ROP) of macrocyclic carbonates (≥12 ring) is still challenging due to the associated low ring-strain. Although organometallic and enzyme based catalysts have been studied, disadvantages such as organometallic residue and enzymic nature limit their applications. After screening commercially available organocatalysts, we report the use of organocatalysts for ROP of disulfide-containing macrocyclic carbonates (MSS, 16 ring). It was found that organocatalysts (TBD) presented high active and living ROP of MSS, as evidenced by kinetic studies, yielding main chain disulfide-containing polycarbonates with tailor-made structures and predictable molecular weights with low molecular weight distribution. Copolymerizations with trimethylene carbonate (TMC) generated random copolymers with controlled components, regulating the density of disulfide functional groups. By comparing with the behaviors of enzyme catalysis in kinetic studies and (co-)polymerization, it is observed that organic catalyzed ROP showed more efficient ( ten times faster), milder condition and more controlled behaviors than enzyme catalyzed ROP (N-435). Therefore, we believe this organic catalyzed strategy will provide an alternative to the current enzymatic and organometallic catalyst for ROP of macrocyclic carbonates.